Pengaruh Leverage, Ukuran Perusahaan, dan Profitabilitas terhadap Biaya audit - Abbas, Dirvi Surya; Rauf, Abdul; Makmun, Syukron; Nurhuda, Hengki (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to examine the effect of leverage, firm size and profitability on audit fee. The population in this study consisted of coal sub-sector mining companies listed on the Indonesia Stock Exchange in 2015-2019. A sample of 8 companies used in this study was determined by the purposive sampling method. The data used is secondary data. Data analysis was carried out with descriptive statistics using panel data regression analysis techniques. The empirical results of this study indicate that Firm Size has a positive effect to audit fee, while profitability and leverage does not have significant effect to the Audit Fee